SP0098 CRYSTAL ARTHROPATHIES: IS THERE A ROLE FOR MRI?. (June 2019) - Hermann, Kay-Geert
Abstract : The plain radiographic features of gout are well known. However, the sensitivity of plain radiographs alone for the detection of signs of gout is poor in acute disease. Dual-energy computed tomography (DECT) and ultrasonography fill the gap for early and specific detection. However, there are instances in which MRI of the painful joints was already acquired. Therefore, it is crucial to know the imaging findings of gout in MRI. MRI per se is not suitable for imaging the calcified bone or soft tissue calcifications. However, there are special techniques such as gradient echo sequences or susceptibility-weighted imaging (SWI) to visualize calcifications. Furthermore, the inflamed joint with all its characteristics such as synovitis, tenosynovitis, and erosions is easily accessible by MRI. Specific findings in the differentiation of RA, PsA, and gout are presented. The presentation will be case-based, and participants will have the opportunity to test their knowledge. Disclosure of Interests: Kay-Geert Hermann Paid instructor for: MSD, AbbVie, Novartis, but less than 10.000€